2013
DOI: 10.1161/circresaha.112.280016
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-10A* and MicroRNA-21 Modulate Endothelial Progenitor Cell Senescence Via Suppressing High-Mobility Group A2

Abstract: Rationale Endothelial progenitor cells (EPCs) contribute to the regeneration of endothelium. Aging-associated senescence results in reduced number and function of EPCs, potentially contributing to increased cardiac risk, reduced angiogenic capacity, and impaired cardiac repair effectiveness. The mechanisms underlying EPC senescence are unknown. Increasing evidence supports the role of microRNAs in regulating cellular senescence. Objective We aimed to determine whether microRNAs regulated EPC senescence and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 33 publications
(47 reference statements)
3
111
0
Order By: Relevance
“…The HMGA2 gene is an established key let-7 target gene in several different cell types (44)(45)(46). Consistent with our results in EC cells, HMGA2 has been shown to be required and sufficient to modulate proliferation, migration, and angiogenesis in endothelial progenitor cells (EPCs) in vitro and the angiogenic capability of bone marrow cells (BMCs) in vivo (51). In an independent study, knockdown of let-7f was shown to repress angiogenesis in a spheroid sprouting assay, suggesting that let-7f may promote angiogenesis (42).…”
Section: Discussionsupporting
confidence: 87%
“…The HMGA2 gene is an established key let-7 target gene in several different cell types (44)(45)(46). Consistent with our results in EC cells, HMGA2 has been shown to be required and sufficient to modulate proliferation, migration, and angiogenesis in endothelial progenitor cells (EPCs) in vitro and the angiogenic capability of bone marrow cells (BMCs) in vivo (51). In an independent study, knockdown of let-7f was shown to repress angiogenesis in a spheroid sprouting assay, suggesting that let-7f may promote angiogenesis (42).…”
Section: Discussionsupporting
confidence: 87%
“…It is estimated that approximately one‐third of all animal genes are controlled by microRNAs, and thus, microRNAs exhibit a wide range of biological processes including aging (Breving & Esquela‐Kerscher, 2010). Indeed, several earlier studies were directed to examine the relationship between microRNAs and endothelial cell senescence (Menghini et al ., 2009; Zhao et al ., 2010; Jong et al ., 2013; Olivieri et al ., 2013; Zhu et al ., 2013). Our present comprehensive microarray analysis revealed that the microRNA with the third highest augmented expression in senescent HUVECs was miR‐22‐3p and that it had a binding site on the 3′ UTR of VASH1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several target genes of miR-10a, including high-mobility group A2 (26), cell adhesion molecule L1-like (27), homeobox (HOX)A1 (28) and HOXD4 (29), which are involved in cellular differentiation, growth, migration and invasion in various pathophysiological processes (26)(27)(28)(29). Other studies have demonstrated that the expression of miR-342-3p is downregulated in the blood and tumor tissues of patients with cancer, including colorectal cancer (30), clinical glioblastoma multiforme (31), breast tumor (32), acute lymphoblastic leukemia (33) and Sézary syndrome (34).…”
Section: Discussionmentioning
confidence: 99%